Characterization and phthalate esters sorption of organic matter fractions isolated from soils and sediments. (November 2015) - Jin, Jie; Sun, Ke; Wang, Ziying; Han, Lanfang; Pan, Zezhen; Wu, Fengchang; Liu, Xitao; Zhao, Ye; Xing, Baoshan
Abstract: The sorption of two phthalate esters (PAEs) and phenanthrene (PHE) by different natural organic matter fractions (NOMs) was examined. The surface area of the NOMs correlated positively with the starting decomposition temperature (SDT), implying increased number of micropores with the rise of condensation. Sorption of PHE on nonhydrolyzable carbons (NHCs) and other NOMs was respectively dependent on aromatic and aliphatic C contents. Likely physical blocking of the aliphatic moieties and input of black carbon materials led to elevated sorption capacity for PHE of aromatic domains in the NHCs. Sorption of PAEs by NOMs excluding NHCs was jointly regulated by hydrophobic partitioning and H-bonding interactions. The SDT of the NOMs correlated negatively with the K oc when SDT ≥304 °C, likely because the highly condensed domains may impair the availability of amorphous moieties for sorption. This study highlights the influence of domain accessibility of NOMs on sorption of hydrophobic organic contaminants. Graphical abstract: Highlights: Sorption of phthalate esters and phenanthrene by organic matter was determined. NHCs and other organic matter fractions exhibited different sorption mechanisms. The K oc correlated inconsistently with the thermal stability of organic matter. The condensed domains would influence the accessibility of amorphous domains. Abstract : The condensed domains of natural organic matter fractions may impair the availability of amorphous moieties for sorption of hydrophobic organic compounds.